Validity of Examination of Complex Specific Antigen Mycobacterium Tuberculosis Rapid Immunochromatography Method in Patients with Pulmonary Tuberculosis - Adrianus Ola Wuan; Marni Tangkelangi; Ni Ketut Yuliana Sari (Journal of Social Research, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which can be transmitted from one person to another by inhaling droplets coughed or sneezed by an infected person. One of the most recent technologies today is the rapid immunochromatography (ICT) method for testing TB antigens. This test detects antigens secreted by Mycobacterium tuberculosis, namely the early secretory antigenic target 6 kDa protein (ESAT6), culture filtrate protein (CFP 10), and Mycobacterium tuberculosis protein (MPT64) encoded by region of difference genes (RDI, RD2, and RD3). The purpose of this study was to determine the validity of TB ICT antigens in diagnosing pulmonary tuberculosis. The research method used is a diagnostic test with a cross-sectional study design. The population of this study was all pulmonary TB patients who were examined at the Prof. Hospital Laboratory. W.Z. John. The samples used in this study amounted to 81 samples which were preceded by smear examination and then 47 samples of M. tuberculosis culture on Lowenstein Jensen media which was used as the gold standard, the results of the examination were 41 samples growing and 6 samples not growing. The sensitivity and specificity of the Rapid ICT TB antigen test were 75.61% and 100%, respectively. The conclusion of the rapid ICT TB antigen test has high validity, so it can be used as an alternative laboratory test for the diagnosis of pulmonary TB.